Memory and Specificity in the Insect Immune System: Current Perspectives and Future Challenges - Cooper, Dustin; Eleftherianos, Ioannis (Frontiers in Immunology, 2017)
The immune response of a host to a pathogen is typically described as either innate or adaptive. The innate form of the immune response is conserved across all organisms, including insects. Previous and recent research has focused on the nature of the insect immune system and the results imply that the innate immune response of insects is more robust and specific than previously thought. Priming of the insect innate immune system involves the exposure of insects to dead, or a sublethal dose of microbes in order to elicit an initial response. Comparing subsequent infections in primed insects to non-primed individuals indicates that the insect innate immune response may possess some of the qualities of an adaptive immune system. Although some studies demonstrate that the protective effects of priming are due to a “loitering” innate immune response, others have presented more convincing elements of adaptivity. While an immune mechanism capable of producing the same degree of recognition specificity as seen in vertebrates has yet to be discovered in insects, a few interesting cases have been identified and discussed.